Multidisciplinary approach for the treatment of maxillary atresia in pediatric dentistry: case report (Research, Society and Development, 2022)
The aim of this clinical case was to report the importance of interceptive orthodontics associated with otorhinolaryngological and speech therapy follow-up in a child diagnosed with maxillary atresia. A 5-year-old white female patient sought dental care complaining of tooth crowding. Clinical evaluation and orthodontic documentation showed Class I molar relationship, Class III canine relationship, convex profile, mandibular incisor retrusion, facial depth with mandibular retrusion, maxillary depth with maxillary retrusion, and small anterior cranial length. The child was evaluated by an otolaryngologist who diagnosed adenoid hypertrophy with borderline airflow, and without indication for adenoidectomy. The proposed treatment was maxillary disjunction with Haas palatine appliance associated with slow expansion of the mandible with a removable expander appliance. In the same period, the child started speech therapy to restore orofacial functions, as she presented low tone of the cheeks and lower lip with mild eversion, shortened upper lip and chin hypertrophy. As for the clinical evolution of the child, there was an increase in orofacial tonus of the lips and cheeks and a decrease in the tonus of the mentalis, a better chewing pattern alternated with more frequent lip closure and better bilabial production during spontaneous speech. It can be concluded that the rapid expansion of the maxilla associated with the slow expansion of the mandible were effective in the treatment of the child, providing good results in the deficiency of the transversal dimension. Moreover, the multidisciplinary approach with Pediatric Dentistry, Otorhinolaryngology and Speech Therapy contributed to the success of the child's therapeutic process.